A study of feasible smart tariff alternatives for smart grid integrated solar panels in India. (15th December 2015) - Thakur, Jagruti; Chakraborty, Basab
Abstract: With the advent of grid connected solar panels in India, the requirement of a separate mechanism for metering and billing is foreseen. The policy framework for addressing this need is under process in various states of India. In the smart grid pilot project at Puducherry, India, a simple net metering mechanism has been incorporated to evaluate and understand the performance of green energy generation through solar panels. The present paper draws a comparison between net metering and gross metering mechanisms, through the analysis of net meter data collected for three different types of consumers from the pilot project at Puducherry. Different scenarios have been evaluated to infer the impacts of specialized billing mechanisms as well as the payback periods on investment made for solar energy systems and the savings that is reflected in the monthly bills. Feed in tariff renders full credit to the renewable energy customers on their electricity bills for the amount of green power, which is sent back to the main grid. This simple mechanism of a credit system would prove to be the most important energy policy for a nation to encourage sustainable energy generation. Due to wide variations in tariffs, requirements and efficiency of utilities across the different states in India, a policy which can accommodate mechanisms of community net metering and aggregate net metering had become a necessity. The paper signifies the crucial and immediate necessity for a feasible and acceptable energy policy so as to realize the benefits of power from the sun. Highlights: Study of net metering data in smart grid pilot project in India. Scenario analysis for savings in electricity under different cases. Comparison of net metering and gross metering mechanisms. Net metering is found to be more beneficial than gross metering. Suggestions for alternative net metering techniques for developing countries.